Monitoring suPAR levels in post-kidney transplant focal segmental glomerulosclerosis treated with therapeutic plasma exchange and rituximab - Nada Alachkar; Jing Li; Dany Matar; Vikas Vujjini; Sami Alasfar; Melissa Tracy; Jochen Reiser; Changli Wei (BMC Nephrology, 2018)
Abstract Background Therapeutic plasma exchange (TPE) is an important therapy for recurrent focal segmental glomerulosclerosis (rFSGS) post kidney transplant. suPAR has been causally implicated in rFSGS, and shown to be a unique biomarker for the occurrence and progression of chronic kidney disease. This study was targeted to evaluate the application of monitoring suPAR in TPE treated rFSGS. Methods A retrospective (n = 19) and a prospective (n = 15) cohort of post transplant FSGS patients treated with TPE and rituximab were enrolled. We measured serum suPAR levels before and after the combined therapies, and assessed the role of suPAR changes on proteinuria reduction and podocyte β3- integrin activity. Results Treatment with TPE and rituximab resulted in significant decrease in proteinuria and suPAR levels. Among the variables including baseline suPAR, serum creatinine, proteinuria, eGFR, age at diagnosis, age at transplantation, transplantation numbers, time to recurrence, and TPE course numbers, only the reduction in suPAR levels and baseline proteinuria significantly correlated with the changes in proteinuria after treatment, with the former performed better in predicting proteinuria alteration. Additionally, the mean podocyte β3 integrin activity significantly decreased after TPE and rituximab treatment (1.10 ± 0.08) as compared to before treatment (1.34 ± 0.08), p < 0.05. Only the reduction in suPAR predicted the response to therapies with an odds ratio of 1.43, 95% CI (1.02, 2.00), p < 0.05. Conclusions Serum suPAR levels reduced significantly after TPE and rituximab treatment in post transplant FSGS patients. The reduction in suPAR levels may be utilized to assess the changes in proteinuria and monitor the response to the therapies. Larger, multi-centered prospective studies monitoring serum suPAR levels in TPE managed post transplant FSGS are warranted.